Flying for a buck or two: Low-cost Carriers in Australia and New Zealand - Gross, Sven; Lück, Michael (European Journal of Transport and Infrastructure Research, 2011)
Over the past few decades, the traditional aviation market has seen significant developments. Traditional “legacy“ carriers have been challenged by new no/low-frills, low cost carriers. While these new airlines have a relatively long history in North America, more recently they successively emerged in markets such as Europe, Asia, Oceania and Africa. The business model of low cost carriers has revolutionized air travel, and both media and academics paid ample attention to these in America and Europe. However, academic literature pertaining to the development of low cost carriers in Australia and New Zealand is scarce. Thus, this paper offers a brief history of low cost carriers in this region, and compares the business models of low cost carriers currently operating in and between Australia and New Zealand. The paper concludes that low cost carriers in this region differ from American and European low cost carriers, in part due to the geography of the countries. The main differences are the levels of in-flight service, and the fact that Australian and New Zealand low cost carriers operate on longer distances, such as coast-to-coast domestic flights in Australia, trans-Tasman flights, and flights to the South Pacific islands, and increasingly to Asia.